2009
DOI: 10.1038/mt.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Nigrostriatal rAAV-mediated GDNF Overexpression Induces Robust Weight Loss in a Rat Model of Age-related Obesity

Abstract: Intraventricular administration of glial cell line-derived neurotrophic factor (GDNF) in primate and humans to study Parkinson's disease (PD) has revealed the potential for GDNF to induce weight loss. Our previous data indicate that bilateral continuous hypothalamic GDNF overexpression via recombinant adeno-associated virus (rAAV) results in significant failure to gain weight in young rats and weight loss in aged rats. Based on these previous results, we hypothesized that because the nigrostriatal tract passes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 46 publications
3
71
1
Order By: Relevance
“…In this study, injection of the POMC vector into either the ARC or the VTA induced TH protein in both the ARC and VTA. Elevated TH protein indicates increased dopamine biosynthesis (Spector et al 1965, Fluharty et al 1985 and is a marker of dopaminergic neurons (Manfredsson et al 2009). Increased hypothalamic TH might be one of the mechanisms contributing to the sympathetic nervous system induction of BAT UCP1.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, injection of the POMC vector into either the ARC or the VTA induced TH protein in both the ARC and VTA. Elevated TH protein indicates increased dopamine biosynthesis (Spector et al 1965, Fluharty et al 1985 and is a marker of dopaminergic neurons (Manfredsson et al 2009). Increased hypothalamic TH might be one of the mechanisms contributing to the sympathetic nervous system induction of BAT UCP1.…”
Section: Discussionmentioning
confidence: 99%
“…This observation raised the possibility that excess GDNF signal in hypothalamic neurons of AAV-GDNF-treated rats acted in extra hypothalamic areas where these cells project, including midbrain dopamine neurons. Consistent with this idea, AAV-GDNF delivery to the midbrain (substantia nigra) elicited decreases in food intake and body weight that were more robust than those induced by delivery to the hypothalamus (Manfredsson et al 2009). Furthermore, a single injection of GDNF into the substantia nigra had an anorexigenic effect that lasted 7-10 days (Hudson et al 1995).…”
Section: Gdnf Supports the Survival And Maturation Of Central Dopaminmentioning
confidence: 78%
“…However, it is important to note that in at least one of the studies involving AAV-GDNF delivery to the midbrain, elevated levels of dopamine were detected in the NAc (Manfredsson et al 2009). Therefore, a contribution of the mesolimbic dopamine pathway cannot be ruled out.…”
Section: Gdnf Supports the Survival And Maturation Of Central Dopaminmentioning
confidence: 97%
“…Specifically, no problems were encountered with respect to stereotactically targeting the SNc, expression of a trophic factor in the SNc, or possible spread to adjacent sites like the ventral tegmental area or hypothalamus. More specifically, we did not observe weight loss, which has been reported as a potential concern for targeting the SN with neurotrophic factors, based on certain preclinical studies, 5,6,11 though others suggested that outcome is likely due to mistargeting protein extending into the ventricles or hypothalamus. 9 We also did not observe any evidence of psychiatric symptoms such as addiction or psychosis that theoretically might result from trophic enhancement of the ventral tegmental area.…”
mentioning
confidence: 76%
“…However, a number of safety concerns have been raised regarding stereotactically targeting the SNc and expressing neurotrophic factors in the substantia nigra (SN) and surrounding structures. [4][5][6] Based on safety associated with targeting the SNc and neighboring regions in patients with PD with deep brain stimulation 7 and fetal tissue transplant, 8 and the lack of serious side effects observed following NRTN gene delivery to the SNc in preclinical studies, 9 we began a clinical trial in patients with advanced PD. In the present article, we present the 24-month results of an open-label safety study of 6 patients who underwent bilateral NRTN gene delivery (CERE-120) to the putamen and SNc.…”
mentioning
confidence: 99%